2014
DOI: 10.1136/jmedgenet-2014-102368
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants within the second intron of theKCNQ1gene affect CTCF binding and confer a risk of Beckwith–Wiedemann syndrome upon maternal transmission

Abstract: This study shows that genetic variants confer a risk of DNA methylation defect with a parent-of-origin effect and highlights the crucial role of CTCF for the regulation of genomic imprinting of the CDKN1C/KCNQ1 domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
0
15
0
1
Order By: Relevance
“…Similarly, detection of the rare but observable structural rearrangements or copy number variations causing subtle imbalances of the subtelomeric 11p15.5 region requires the integrated application of multicolor fluorescence in situ hybridization (FISH), high-resolution array comparative genomic hybridization (CGH), or SNP array [ 17 20 ]. Cis- and trans-acting factors responsible for complex interactions between the 11p15.5 imprinted genes have been identified in both BWS and SRS [ 7 , 21 , 22 ]; however, they are not included in the current diagnostic flowchart as no precise information is available on the fraction of cases accounted for by these mechanisms. Although this point is being addressed by ongoing research, diagnostic laboratories must combine all the indicated approaches to obtain the highest possible detection rate (>80 %) of (epi)genetic alterations in SRS and BWS.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, detection of the rare but observable structural rearrangements or copy number variations causing subtle imbalances of the subtelomeric 11p15.5 region requires the integrated application of multicolor fluorescence in situ hybridization (FISH), high-resolution array comparative genomic hybridization (CGH), or SNP array [ 17 20 ]. Cis- and trans-acting factors responsible for complex interactions between the 11p15.5 imprinted genes have been identified in both BWS and SRS [ 7 , 21 , 22 ]; however, they are not included in the current diagnostic flowchart as no precise information is available on the fraction of cases accounted for by these mechanisms. Although this point is being addressed by ongoing research, diagnostic laboratories must combine all the indicated approaches to obtain the highest possible detection rate (>80 %) of (epi)genetic alterations in SRS and BWS.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a single-nucleotide polymorphism (SNP) in the 5 0 region of the H19 gene and located near CTCF-binding sites has been associated with abnormal birth weight in humans, with a decrease or increase in birth weight, depending on the parental origin of allele [128]; furthermore, SNPs located in critical CTCF and OCT4 binding sites of the H19 ICR region have been associated with increased hypermethylation of specific CpG sites of the maternal H19 allele [129,130] in BWS patients [130], which, in turn, may affect CTCF binding and subsequent IGF 2 expression and growth. Additionally, SNPs in another imprinted gene, KCNQ1, affect CTCF binding to DNA and also correlate with BWS risk [131]. CTCF is also involved, in a methylation-dependent manner, in the modulation of genetic repeat instability, which, in turn, is related to several human disorders resulting from microsatellite expansion [132].…”
Section: Ctcf Fertility and Artsmentioning
confidence: 99%
“…[33][34][35] Intronic methylation has been shown to have functional relevance to human disease outcomes; differential methylation of gene variants within the second intron of KCNQ1 affects CTCF binding and confers risk for Beckwith-Wiedemann syndrome, an overgrowth disorder linked to epigenetic defects at imprinted genes. 36 Functional relevance of intronic methylation patterns in mice has been shown, as well. Intronic enhancer activity in the murine sf-1/ad4bp gene is correlated with both DNA methylation pattern and tissue-specific gene expression.…”
Section: Assay Forward Primermentioning
confidence: 99%